Transformation of the myth and the myth of transformation: over 100 years of guiding in South African game reserves - Paton, Anthony James (My University, 2008)
This is both a critical history of the nature guiding industry in South Africa from 1902- 2007 and a subjective critique of the practical components of contemporary natureguiding. It focuses particulary on guides operating on foot in “Big Five” (dangerous game) areas. The early history and the subsequent development of “wilderness” trails in the Kruger National Park and the histories of KwaZulu-Natal Parks and Madikwe Game Reserve are examined. The influences of the Field Guides’ Association of Southern Africa (FGASA) and the Tourism, Hospitality and Sport Education and Training Authority (THETA) are discussed. Transformation of the industry (in both the demographic and in the broader sense) faces language, cultural and ethical challenges because of prevailing anthropocentric and militaristic norms. Nature guides need improved communication skills and should balance traditional and progressive skills and ethics. They should become more critical and proactive in determining the style and content of their industry
Keywords: "Big Five"; Dangerous game; Kruger National Park; KwaZulu-Natal Parks/KwaZulu-Natal Wildlife; Nature guides; Nature guiding; Madikwe Game Reserve; Field Guides Association of Southern Africa/FGASA